The Use of Humoral Responses as a Marker of CMV Burden in HIV Patients on ART Requires Consideration of T-Cell Recovery and Persistent B-Cell Activation - Brunt, S.; Lee, S.; D'Orsogna, L.; Bundell, C.; Burrows, S.; Price, Patricia (Hindawi Publishing Corporation, 2014)
Objectives. Elevated humoral responses to cytomegalovirus (CMV) associate with increased risk of cardiovascular disease (CVD) in HIV patients on antiretroviral therapy (ART). To better understand the persistence of CMV humoral responses in relation to CVD, we determined trends in CMV antibody levels over the first 10 years on ART. Design. We describe longitudinal analyses of plasma from 13 HIV patients commencing ART with <210 CD4 T-cells/µL and 27 controls. Antibodies reactive with CMV (fibroblast lysate, gB and IE-1 antigens), EBV-VCA, and HIVgp41 were quantitated. B-cell activation was assessed via total IgG and sBAFF. Inflammation was assessed via sTNF-RI and sCD14. Results. Amongst CMV seropositive HIV patients, levels of antibody reactive with CMV and EBV-VCA peaked after 1 year on ART. Levels of total IgG, sCD14, and sTNF-RI declined to approximate those in controls after 10 years, but sBAFF , EBV-VCA , and CMV antibodies remained elevated. A strong correlation between sBAFF and CMVgB antibody was seen at 10 years and verified in a second cohort. Conclusions. CMV antibody titres peak on ART and remain high. A correlation between CMV antibody and sBAFF suggests a role for HIV-induced B-cell pathology that may affect its use as a marker of CMV burden.